Cody

# Problem 2073. Split a given string from the first instance of a given character

Solution 1914395

Submitted on 28 Aug 2019
This solution is locked. To view this solution, you need to provide a solution of the same size or smaller.

### Test Suite

Test Status Code Input and Output
1   Fail
x='I want to split this: from this'; [y1,y2] = SplitString(x,':'); y1_correct = 'I want to split this'; y2_correct = ': from this'; assert(isequal(y1,y1_correct)) assert(isequal(y2,y2_correct))

t = 17 y1 = 'I want to split ' y2 = 'this: from this'

Assertion failed.

2   Fail
x='This one does not have the divider'; [y1,y2] = SplitString(x,':') y1_correct = 'This one does not have the divider' y2_correct = '' assert(isequal(y1,y1_correct)) assert(isequal(y2,y2_correct))

t = [] y1 = 1×0 empty char array y2 = 1×0 empty char array y1 = 1×0 empty char array y2 = 1×0 empty char array y1_correct = 'This one does not have the divider' y2_correct = 0×0 empty char array

Assertion failed.

3   Fail
x='This sentence should, not have a comma.'; [y1,y2] = SplitString(x,',') y1_correct = 'This sentence should' y2_correct = ', not have a comma.' assert(isequal(y1,y1_correct)) assert(isequal(y2,y2_correct))

t = 15 y1 = 'This sentence ' y2 = 'should, not have a comma.' y1 = 'This sentence ' y2 = 'should, not have a comma.' y1_correct = 'This sentence should' y2_correct = ', not have a comma.'

Assertion failed.

4   Pass
x='Divide only @ at the @ first instance of @.'; [y1,y2] = SplitString(x,'@') y1_correct = 'Divide only ' y2_correct = '@ at the @ first instance of @.' assert(isequal(y1,y1_correct)) assert(isequal(y2,y2_correct))

t = 13 22 42 y1 = 'Divide only ' y2 = '@ at the @ first instance of @.' y1 = 'Divide only ' y2 = '@ at the @ first instance of @.' y1_correct = 'Divide only ' y2_correct = '@ at the @ first instance of @.'

5   Fail
x='Take that, and this, and something else.'; [y1,y2] = SplitString(x,',') y1_correct = 'Take that' y2_correct = ', and this, and something else.' assert(isequal(y1,y1_correct)) assert(isequal(y2,y2_correct))

t = 6 16 y1 = 'Take ' y2 = 'that, and this, and something else.' y1 = 'Take ' y2 = 'that, and this, and something else.' y1_correct = 'Take that' y2_correct = ', and this, and something else.'

Assertion failed.